2021
DOI: 10.3390/nu13020472
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Nutritional Supplements and Dietary Interventions on Placental Complications: An Umbrella Review, Meta-Analysis and Evidence Map

Abstract: The placenta is a vital, multi-functional organ that acts as an interface between maternal and fetal circulation during pregnancy. Nutritional deficiencies during pregnancy alter placental development and function, leading to adverse pregnancy outcomes, such as pre-eclampsia, infants with small for gestational age and low birthweight, preterm birth, stillbirths and maternal mortality. Maternal nutritional supplementation may help to mitigate the risks, but the evidence base is difficult to navigate. The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 342 publications
1
32
0
Order By: Relevance
“…A meta-analysis restricted to LMIC reported a significant effect of omega-3 supplementation on preeclampsia (RR 0.40, 95% CI: 0.21-0.77, I 2 0%, six studies, N=1343), but there was no difference in severe preeclampsia, eclampsia, or gestational hypertension. 133 There are also some intriguing possibilities that deserve further studies, including periconceptional vitamins, [135][136][137] dietary nitrates, 138 reduced sodium intake 139 and antioxidants other than vitamins C and E, but thus far none have been of proven benefit. 140 Omega-3 supplementation reduced the risk of early preterm delivery at < 34 weeks (RR 0.42, 95% CI 0.27-0.66, p=0.0002, 6 studies, n=4193) and any preterm birth (RR 0.83, 95% CI 0.70-0,98, p=0.03, 9 studies, n=5980) according to a systematic review.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis restricted to LMIC reported a significant effect of omega-3 supplementation on preeclampsia (RR 0.40, 95% CI: 0.21-0.77, I 2 0%, six studies, N=1343), but there was no difference in severe preeclampsia, eclampsia, or gestational hypertension. 133 There are also some intriguing possibilities that deserve further studies, including periconceptional vitamins, [135][136][137] dietary nitrates, 138 reduced sodium intake 139 and antioxidants other than vitamins C and E, but thus far none have been of proven benefit. 140 Omega-3 supplementation reduced the risk of early preterm delivery at < 34 weeks (RR 0.42, 95% CI 0.27-0.66, p=0.0002, 6 studies, n=4193) and any preterm birth (RR 0.83, 95% CI 0.70-0,98, p=0.03, 9 studies, n=5980) according to a systematic review.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“… 129 Therapy with vitamins C and E as administered in several large studies has not proven effective to prevent preeclampsia. 130 , 131 Several other micronutrients, including folic add, 132 , 133 vitamins A and D, 133 zinc, 134 iodine, 135 omega-3 FAs, 136 and arginine, 137 are supported by some, but not all, supplementation studies. A meta-analysis restricted to LMICs reported a significant effect of omega-3 supplementation on preeclampsia (risk ratio [RR], 0.40; 95% confidence interval [CI], 0.21–0.77; I 2 , 0%; 6 studies, n=1343), but there was no difference in severe preeclampsia, eclampsia, or gestational hypertension.…”
Section: The Consumption Of a Beneficial Dietary Pattern Before And D...mentioning
confidence: 99%
See 1 more Smart Citation
“…Fixed-effects meta-analysis of the RCTs indicated that vitamin D supplementation was a prevention factor for pre-eclampsia; however, random-effects meta-analysis of trials found no significant association between vitamin D and pre-eclampsia 80. The most recent summary (2021) described itself as an ‘umbrella analysis’ and found a reduced risk of developing pre-eclampsia among pregnant women who received vitamin D supplementation (RR 0.62, 95% CI 0.43 to 0.91, I 2 =0%, 12 studies, n=1353) 85…”
Section: Resultsmentioning
confidence: 99%
“…The International Fetal and Newborn Growth Consortium (INTERGROWTH‐21 st ) study demonstrated similar fetal growth in eight geographically defined urban populations, when controlled for nutrition, antenatal care, and environmental growth constraints, suggesting that at least some SGA is modifiable 16,21 . Inflammation from malnutrition, infection, or helminth infestation has been implicated in the pathogenesis of several adverse obstetric outcomes, 22,23 but might not generate the placental angiogenic profile traditionally associated with SGA. An investigation of circulating sEng levels in pregnant women from Malawi and Cameroun reported higher levels of sEng in primigravid women—the demographic that trended towards higher incidence of SGA in this sample—and showed higher sEng concentrations with both infection and fetal growth restriction 24 .…”
Section: Discussionmentioning
confidence: 99%